Integrative Few-Shot Classification and Segmentation for Landslide Detection - Dat Tran-Anh; Bao Bui-Quoc; Anh Vu-Duc; Trung-Anh Do; Hung Nguyen Viet; Hoai-Nam Vu; Cong Tran (IEEE Access, 2022)
There has been an ongoing demand for monitoring landslides due to the heavy economic losses and casualties caused by such natural disasters. In this paper, we introduce a swift landslide detection system that can detect and segment landslides occurring on roads. To tackle the challenges of data collection, we propose an automatic annotation procedure to create a new landslide dataset consisting of 2963 images, termed the LandslidePTIT dataset. Additionally, we construct a novel deep-learning architecture that can perform both classification and segmentation tasks well from a few annotated images of landslides. Specifically, the model consists of four main modules that are delicately designed to solve the few-shot segmentation problem using landslide images, namely hypercorrection construction, attentive squeeze block, a cross-feature layer, and broadcast and squeeze layer. Experimental results exhibit the superiority of the proposed method in comparison with competitive baselines, in terms of both quantitative and qualitative manners.